Bacterial infection and microbiota in carcinogenesis and tumor development - Li, Qiao (Frontiers in Cellular and Infection Microbiology, 2023)
Microbiota colonize exposed body tissues (e.g., gastrointestinal tract, skin, lungs, female genital tract, and urogenital tracts) and unexposed sites (e.g., breast). Persistent bacterial infection in the host lead to the development of multiple disease. They are implicated in the pathogenesis of various complex diseases, including diabetes, atherosclerosis, autoimmune diseases, Alzheimer's disease, and malignant diseases. Amounting studies have demonstrated the role of bacterial infection in carcinogenesis. The study of microbiota in tumorigenesis is primarily focused on lung cancer, colorectal cancer (CRC), breast cancer, gastric cancer, and gynecologic tumors, and so on. Infection of Helicobacter pylori in gastric cancer carcinogenesis is recognized as class I carcinogen by the World Health Organization (WHO) decades ago. The role of Fusobacterium nucleatum in the development of colorectal cancer is extensively investigated. Variable bacteria have been cultured from the tumor tissues. The identification of microbiota in multiple tumor tissues reveal that bacterial infection and microbiota are associated with tumor development. The microbiota affects multiple aspects of carcinogenesis and tumor development, including favoring epithelial cells proliferation, establishing inflammatory microenvironment, promoting metastasis, and causing resistance to therapy. On the other hand, microbiota can shape a tumor surveillance environment by enhancing cell activity, and sensitize the tumor cells to immune therapy. In the present review, the roles of microbiota in multiple malignancies are summarized, and unraveling the mechanisms of host-microbiota interactions can contribute to a better understanding of the interaction between microbiota and host cells, also the development of potential anti-tumor therapeutic strategies.